Attachment Styles and Suicide-Related Behaviors in Adolescence: The Mediating Role of Self-Criticism and Dependency - Falgares, Giorgio; Marchetti, Daniela; De Santis, Sandro; Carrozzino, Danilo; Kopala-Sibley, Daniel C.; Fulcheri, Mario; Verrocchio, Maria Cristina (Frontiers in Psychiatry, 2017)
Insecure attachment and the personality dimensions of self-criticism and dependency have been proposed as risk factors for suicide in adolescents. The present study examines whether self-criticism and dependency mediate the relationship between insecure attachment styles and suicidality. A sample of 340 high-school students (73.2% female), ranging in age from 13 to 20 years (M = 16.47, SD = 1.52), completed the Depressive Experiences Questionnaire for Adolescents (DEQ-A), the Attachment Style Questionnaire (ASQ), and the Suicidal Behaviors Questionnaire-Revised (SBQ-R). The results partially support the expected mediation effects. Self-criticism, but not dependency, mediates the link between insecure attachment (anxiety and avoidance) and suicide-related behaviors. Implications for suicide risk assessment and management are discussed.